2007
DOI: 10.1007/s10803-007-0450-9
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Checklist for Autism in Toddlers: A Follow-up Study Investigating the Early Detection of Autism Spectrum Disorders

Abstract: Autism spectrum disorders (ASD) often go undetected in toddlers. The Modified Checklist for Autism in Toddlers (M-CHAT) was used to screen 3,793 children aged 16-30 months from lowand high-risk sources; screen positive cases were diagnostically evaluated. Re-screening was performed on 1,416 children aged 42-54 months. Time 1 Positive Predictive Value (PPV) was .36 for the initial screening and .74 for the screening plus follow-up telephone interview; values were similar for Time 2 PPV. When separating referral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
270
3
38

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 357 publications
(324 citation statements)
references
References 49 publications
13
270
3
38
Order By: Relevance
“…13 It also confirms previous studies showing that most children with false-positive screens have developmental difficulties 17 of a degree that would make them eligible for early intervention. Some children with false-positive screens had atypical features not meeting criteria for ASD.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…13 It also confirms previous studies showing that most children with false-positive screens have developmental difficulties 17 of a degree that would make them eligible for early intervention. Some children with false-positive screens had atypical features not meeting criteria for ASD.…”
Section: Discussionsupporting
confidence: 84%
“…8 Another study in community practices reported that this follow-up procedure increased the positive predictive value (PPV) from 0.11 to 0.65, reinforcing the need for the follow-up interview. 13 The interview consists of a script that prompts for specific examples of behaviors relevant to each failed item. Based on the parent's responses, the interviewer may change failed items to a pass.…”
mentioning
confidence: 99%
“…The M-CHAT, also adapted from the CHAT, has been assessed in large community [25][26][27] the PPV of the M-CHAT for ASD was 0.54, and for any developmental disorder, it was 0.98. 31 As in other communitybased ASD-screening studies, estimates of PPV were based on those screen-positive children who attended and completed a diagnostic evaluation (39.3% of screen-positive children were not assessed).…”
Section: M-chatmentioning
confidence: 99%
“…M-CHAT includes a checklist of 23 items to be filled out by parents and it can be administered at a much earlier stage to identify toddlers who are at risk of autism. A recent study has confirmed the validity of this instrument in detecting possible ASD at 16-30 months of age (Kleinman et al, 2008). However, the high sensitivity of this checklist means that some children without autism will fail the screening.…”
Section: Diagnostic Approachesmentioning
confidence: 89%